The use of Translanguaging in assisting educators to teach African languages: A case study of Tshwane South Education District, Pretoria - Gobodwana, Anele (School of Languages and Literatures, 2023)
South Africa is a diverse and multicultural country with too many more spoken indigenous languages. It is also one of the fastest developing countries on the African continent. This multilingual nature coupled with migration from neighbouring countries, presents serious challenges for language planners and education authorities, especially the impact on education. This study, therefore, explores the use of Translanguaging and how it has facilitated the teaching of African languages in multilingual classrooms at the Tshwane South Education District in Gauteng Province. The primary objective of the research happened to track the transitioning of dialect or variant development across different grades in these multilingual areas. The secondary aim was to observe and document language practices in these schools to provide a firm base for future language planning efforts in South Africa. The research was conducted in two schools: one primary school and one high school. The focus of the study was on the entry and final standards of the fundamental classes, the middle classes, the exit primary classes (standard 5), and entry classes (standard 6), up until the year of schooling (standard 10). The data were collected using interviews, questionnaires as well as observation. The data were subjected to thematic analysis to get an in-depth understanding as well as to identify and generate new insights into Translanguaging. Whereas many of the educators speak more than one language, many were not aware of their Translanguaging practices in teaching. The participating educators also affirmed that they have been using Translanguaging without realising it. Educators further indicated that raising awareness about their language practices facilitated their teaching because they felt at ease switching and mixing languages in their teaching. In addition to the positive outcome, some educators alluded to the fact that in some areas they were faced with language barriers. The study therefore recommends that in addition to raising awareness amongst educators, the Department of Education and the Fundza Lushaka Bursary scheme should assess the language repertoires of teachers before commencement of employment. The study further recommends that language policy makers and planners need to be mindful of the impact of multilingualism and migration on the education system.